A Glitch in the Matrix: The Role of Extracellular Matrix Remodeling in Opioid Use Disorder - Ray, Madelyn H.; Williams, Benjamin R.; Kuppe, Madeline K.; Bryant, Camron D.; Logan, Ryan W. (Frontiers in Integrative Neuroscience, 2022)
Opioid use disorder (OUD) and deaths from drug overdoses have reached unprecedented levels. Given the enormous impact of the opioid crisis on public health, a more thorough, in-depth understanding of the consequences of opioids on the brain is required to develop novel interventions and pharmacological therapeutics. In the brain, the effects of opioids are far reaching, from genes to cells, synapses, circuits, and ultimately behavior. Accumulating evidence implicates a primary role for the extracellular matrix (ECM) in opioid-induced plasticity of synapses and circuits, and the development of dependence and addiction to opioids. As a network of proteins and polysaccharides, including cell adhesion molecules, proteases, and perineuronal nets, the ECM is intimately involved in both the formation and structural support of synapses. In the human brain, recent findings support an association between altered ECM signaling and OUD, particularly within the cortical and striatal circuits involved in cognition, reward, and craving. Furthermore, the ECM signaling proteins, including matrix metalloproteinases and proteoglycans, are directly involved in opioid seeking, craving, and relapse behaviors in rodent opioid models. Both the impact of opioids on the ECM and the role of ECM signaling proteins in opioid use disorder, may, in part, depend on biological sex. Here, we highlight the current evidence supporting sex-specific roles for ECM signaling proteins in the brain and their associations with OUD. We emphasize knowledge gaps and future directions to further investigate the potential of the ECM as a therapeutic target for the treatment of OUD.